Cas3 nuclease activity is regulated by an iHDA1 region located at the interface between HD and RecA1 domain - He, Liu (2022)
CRISPR Cas3 is a crucial protein effector for type I CRISPR interference. It couples actions of helicase and nuclease domains to eliminate mobile genetic elements (MGEs) in response to the recognition of protospacer sequences on foreign DNA by the Cascade complex that recruits Cas3. The DNA cleavage efficacy of Cas3 determines whether or not the host cell survives infection caused by MGEs. Cascade stimulates Cas3 DNA hydrolysis activity, and Cas3 possesses structure and functions characteristics that are Cascade-independent and may be additionally modulated by other factors. These challenges previous understanding of Cas3 mechanism in CRISPR interference and in potentially other aspects of bacterial physiology. This work reported in this thesis investigated Cas3 structure-function. A crucial Cas3 region, termed iHDA1, is highlighted for its role in determining whether DNA can access the Cas3 HD nuclease sites. This iHDA1 region accommodates the Trp-406 amino acid that can cause a steric block in the DNA channel within Cas3; therefore, we define this tryptophan amino acid as a ‘gate’. Extrinsic factors also impact Cas3 function, we propose by stimulating the iHDA1 region to undergo conformational changes. As reported here, these are temperature, the CRISPR adaptation protein Cas1, and a predicted post-translational modification targeting a predicted redox switch in the iHDA1 region. In addition, a novel protein interaction between Cas3 and DNA polymerase I was discovered.